Claudin-18 expression under hyperoxia in neonatal lungs of bronchopulmonary dysplasia model rats - Zuo, Jingye; Tong, Yajie; Yang, Yuting; Wang, Yirui; Yue, Dongmei (Frontiers in Pediatrics, 2022)
Background: Bronchopulmonary dysplasia (BPD) is characterized by impaired alveolar and microvascular development. Claudin-18 is the only known lung-specific tight junction protein affecting alveolar epithelium development and transdifferentiation. Objective: To explore the changes in claudin-18 expression, alveolar epithelial cell (AEC) marker proteins, the canonical WNT pathway, and their possible regulatory relationships in a hyperoxia-induced BPD rat model. Methods: The BPD neonatal rat model was established by exposure to hyperoxia (85%). Hematoxylin and eosin (HE) staining was used to confirm the establishment of the BPD model. The mRNA levels were assessed using quantitative real-time polymerase chain reaction, while protein expression levels were determined using western blotting, immunohistochemical staining, and immunofluorescence. Results: As confirmed by HE staining, the BPD neonatal rat model was successfully established. Compared with the air group, claudin-18 and claudin-4 expression decreased in the hyperoxia group. The expression of β-catenin of the WNT signaling decreased, whereas that of p-GSK-3β increased. Expression of the AEC Ⅱ marker SFTPC decreased initially and then increased, whereas that of the AEC Ⅰ marker podoplanin increased on day 14 (P < 0.05). Conclusions: Claudin-18 downregulation during hyperoxia may affect lung development and maturation, which may result in hyperoxia-induced BPD. Additionally, claudin-18 is associated with the canonical WNT pathway and alveolar epithelial transdifferentiation.